(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The purpose of the research is to develop a scientifically based model of integrating folk pedagogy traditions into the modern system of labor education of youth based on an analysis of the pedagogical potential of ethnopedagogical tools and methods. The research used theoretical methods (analysis, synthesis, systematization, modeling), empirical methods (pedagogical observation, questionnaire, interview), as well as mathematical statistical methods for processing the data obtained. The integration of folk pedagogy traditions into the modern system of labor education helps to form stable labor values in young people, develop practical skills and qualifications, and strengthen ties with national cultural traditions. The effectiveness of the process is ensured by the comprehensive use of folk-pedagogical tools in compliance with the identified pedagogical conditions.